Religious co-existence in Malappuram : myth or reality - Muhammed, Muneer Kuttiyani (International Islamic University Malaysia, 2013)
Hindu-Muslim relation in Malappuram district of Kerala state in India is noteworthy in terms of its peaceful co-existence since the early Muslim presence in the region. However, there are some attempts that have been taking place to polarize the people of both communities, just like what the colonizers did during the period of colonial invasion. The purpose of the present study is to determine the status of religious co-existence prevailing in the current social realm of Malappuram in relation to its historical contributions towards Hindu-Muslim peaceful co-existence. The study also seeks the critical analysis of the denunciations put against the district and its people, which threatened the idea of peaceful co-existence and its practicability. The study examines the history, status and features of Religious co-existence in the district. The perception of Hindus on the majority Muslims have also been highlighted in the study. The methodology of the research is qualitative analysis through library study and examination of relevant information based on books, articles, websites, newspapers, reports of various agencies including the interviews of selected personalities. This study highlights the need for a peaceful inter-religious ambience in a society where different people of different faiths live together. The sustenance of the peaceful co-existence between the Muslims and Hindus can be maintained by reiterating the glorious history of the region which has been heavily emphasized in this study.